Architecture and properties of anisotropic polymer composite scaffolds for bone tissue engineering - Mathieu, L.M.; Mueller, T.L; Bourban, P-E.; Pioletti, D.P.; Muller, R.; Manson, J-A.E.
Bone is a complex porous composite structure with specific characteristics such as viscoelasticity and anisotropy, both in morphology and mechanical properties. Bone defects are regularly filled with artificial tissue grafts, which should ideally have properties similar to those of natural bone. Open cell composite foams made of bioresorbable poly(L-lactic acid)(PLA)and ceramic fillers, hydroxyapatite (HA)or b-tricalcium phosphate (b-TCP), were processed by supercritical CO2 foaming. Their internal 3Dstructure was then analysed by micro-computed tomography (mCT), which evidenced anisotropy in morphology with pores oriented in the foaming direction. Furthermore compressive tests demonstrated anisotropy in mechanical behaviour, with an axial modulus up to 1.5 times greater than the transverse modulus. Composite scaffolds also showed viscoelastic behaviour with increased modulus for higher strain rates. Such scaffolds prepared by gas foaming of polymer composite materials therefore possess suitable architecture and properties for bone tissue engineering applications.
Keywords: COMPOSITE; SCAFFOLD; COMPRESSION; MICROCT; ANISOTROPY